Toward the development of an economically viable digital x-ray imaging device - Mlambo, Musikavanhu Roy (My University, 2010)
A project aimed at the development of a robot-based patient positioning system for high-precision proton radiotherapy is underway at iThemba LABS. Part of the project included the development of a portal digital x-ray imaging device that would be used to verify the patient treatment set-up. The imaging device consisted of a scintillation screen, front surface mirror and a high-resolution charged-couple device (CCD) camera. The total costs for the device were about 7 times less expensive than a commercial amorphous silicon flat panel detector. To improve the efficiency of the system, the CCD chip and scintillation screen were chosen so that the wavelength of the light from the screen closely matched the wavelength at which the CCD sensor has the maximum quantum efficiency. The digital images compared favourably with those of x-ray film. Although the digital images were of lower resolution due to the finite resolution of the CCD chip, they were considered satisfactory. The use of pixel binning allowed for the use of lower exposure settings when compared to exposure settings for un-binned images. This resulted in a reduction of patient dose without significantly compromising image quality. The device would not be used for diagnostic purposes, but only to verify patient position at treatment setup. As such, the digital images would be compared against digitally reconstructed radiographs (DRRs) of the fields and/or the treatment position, which are created from the treatment planning Computed Tomography (CT) images. In general, the spatial resolution of the DRRs is also comparably lower than digital x-ray images, as the resolution of the DRRs is limited to the voxel size of the CT images.